Nordafrikanische Trockensteppengesellschaften.: Zur ökologischen Erklärung der räumlichen Differenzierung der Vegetation zwischen Mittelmeer und Sahara - Müller-Hohenstein, Klaus (ERDKUNDE, 1978)
In contrast to the Mediterranean and even to the northern Sahara the vegetation of the North African belt of arid steppe has so far only been accorded description in surveys of relatively large areas. This study represents an attempt to make a more exact registration of the most significant plant societies of this region in the case of the high plateau of eastern Morocco. Defined on the basis of plant sociology Stipa tenacissima and Artemisia herba-alba societies and their distribution patterns are discussed and explained with the help of selected parameters of edaphic and climatic variants. The results are indispensable as a basis for further investigations of the economic potential of regions of arid steppe.